A spatial hedonic approach to water recreation value - Artell, Janne (it, 2011)
Very few studies have addressed the value of water quality in a hedonic property price setting. In this study we elicit the value of improved water quality capitalized in recreational property prices adjacent to the Baltic Sea, lakes and rivers. Additionally we employ spatial econometric methods to address spatial autocorrelation found in data. We use an expert determined, water body specific water quality index that describes the usability status of the water instead of more specific but also more problematic water quality indicators. We find water usability to have a positive and non-linear effect on property prices, where extreme water quality conditions result in statistically significant price effects. The non-linearity implies a strong support for protection of water quality.
Keywords: Ma; vesistöjen virkistyskäyttö; veden laatu; recreational areas; water quality